Centering Justice in a Sustainable Food Systems Master's Program - Greeson, Kimberley M.; Currey, Robin C. D. (Frontiers in Sustainable Food Systems, 2021)
The new Master of Science in Sustainable Food Systems (MSFS) program at Prescott College was re-envisioned as part of the preferred teach out partnership with Green Mountain College that closed in 2019. In collaboration with faculty from both colleges, the new MSFS program was developed to intentionally center social justice and offer students a Food Justice concentration. Food justice is a growing movement that seeks to shift global, industrial food systems toward more equitable, just, and sustainable foodways. Using this definition, students in the Food Justice core course uncovered how forms of institutional oppression prevent certain communities from accessing healthy and culturally appropriate food. This course was designed and taught from an anti-racist, anti-colonial, and culturally sustaining pedagogical framework. The Food Justice course frames students' investigation of the current food system and how issues of privilege, access, and identity relate to food justice throughout the MSFS program. Through experiential learning, students were asked to develop and implement a project that aligns with social justice values. In this perspective paper, we describe our experiences as sustainable food systems educators in making structural changes to the master's program. We share the values and assumptions that led to the development of the Food Justice concentration and course; detail our pedagogical frameworks; and highlight students' projects as a manifestation of the student experience.